Analysis of Crude Fiber Content in Chips - Rona Safrina; Arif Saputra; Muhammad Suryana; Nurhaliza Nurhaliza; Ropita Ropita; Nopia Nopia (Journal of Food Security and Agroindustry, 2026)
This study aims to determine the crude fiber content in potato chip samples. Potato chips were chosen because they are a processed food product commonly eaten as a snack and are commonly consumed by the public. The crude fiber test is a method for determining the insoluble content of food samples, such as vegetables, tubers, or fruit. The method used in this study was quantitative with an experimental approach. The samples used were purple sweet potato chips, banana chips, and orange chips, each with different oven-drying methods. The drying time for chips was 1 hour. The results of this study indicate that purple sweet potato chips (4.462%-6.241%) have a relatively high crude fiber content, compared to the other two samples. The high fiber content in purple sweet potato may be due to its thicker fiber network compared to the other two samples. In addition, factors such as the maturity level of the tuber, growing conditions, and processing methods can affect the fiber content obtained. Based on these results, purple sweet potato is a healthy food that can be a healthy snack and can be used to increase fiber intake in the daily diet.